Методы вычисления потерь мощности в элементах несимметрично нагруженной сети - Мирошник, A.A. (Електротехніка і електромеханіка, 2011)
Methods of approximate and exact calculation of power losses in irregularly loaded 0.38 / 0.22 kV networks are introduced.